Eficácia clínica do dipropionato de imidocarb associado à ciprofloxacina contra a tristeza parasitária bovina - Casas, Juliana Bonamim de Castro (2018)
The present research studied Imidocarb dipropinate to treat Babesia spp associated with Ciprofloxacin against Anaplasma marginale. Six male calves, one and four months old, were experimentally infected at three different times with inoculation of fresh blood collected from three adult animals, naturally infected by Babesia spp and A. marginale. Rectal temperature, hematocrit and direct blood smear tests were performed to confirm infection, treatment was instituted with a single dose of 1.2 mg / kg Imidocarb Dipropinate associated with 7.5 mg / kg Ciprofloxacin intramuscularly. After treatment of the first, second and third inoculation, respectively, the rectal temperature returned to the normal values on the days 10.3 ± 10.3, 12.5 ± 4.1 and 2.5 ± 2.1 days, respectively, hematocrit normalized on average 25.5 ± 4.5, 10.8 ± 5.8 and 6.2 ± 5.3 days. All animals returned to the normal parameters of the species, there were no records of clinical complications, requirement for supportive treatments or disease progression after treatment. In view of the established methodology and results obtained the combination of the products resulted in a satisfactory clinical response with only a single dose.